Inside Windows NT infrastructures. - Iseminger, David, 1969- (John Wiley & Sons, Inc., 1998)
"There are lots of authors who can explain how to install Windows NT, and no end of tomes telling you more than you ever needed to know about how NT works. But where do you go for answers to real questions like these? When it comes to questions of scaleup, cabling, performance tradeoffs, remote access, and all the other nuts-and-bolts issues with which network professionals grapple, there's only one place to go-the source. Inside Windows NT Infrastructures was written by someone who has worked in the Microsoft Windows NT Group for years. The crucial tips, techniques, and rules of thumb it contains were obtained the hard way-by running NT on hundreds of machines, in countless environments, and under real-life deployment conditions. As a result, it is the most authoritative source of practical information on such key administration and management issues as planning your infrastructure, networking protocols, routing, backbones, server sizing, interoperability, security, and more. Other hot topics covered in detail include: • Choosing the best domain model for your operation. • Switches versus hubs. • Ensuring reliability and performance within your deployment. • Remote access that really Works. • Choosing hardware and software wisely. For complete practical solutions to all your Windows NT networking issues, turn to the source, Inside Windows NT Infrastructures." (Copied from the past).